Accidental exposure to glimepiride from adulterated medication resulting in severe hypoglycaemia. (1st June 2022) - Hayes, Annabelle G; Umapathysivam, Mahesh M; Torpy, David J
Abstract : Summary: Sulphonylureas are insulinotropic and are not only useful in patients with diabetes but also act in non-diabetic individuals where hypoglycaemia and hyperinsulinism mimic insulinoma. We present a 63-year-old man who presented with inadvertent sulphonylurea-induced life-threatening hypoglycaemia on two occasions, resulting in hazardous and invasive investigation. Biochemistry revealed endogenous hyperinsulinaemia, with elevated serum c-peptide and insulin concentrations during symptomatic hypoglycaemia, and plasma glucose of 1.7 mmol/L. There was no history of sulphonylurea use prompting anatomical insulinoma studies to locate an insulinoma. However, a routine plasma insulinoma screen-detected glimepiride. Directed history implicated a medication taken for erectile dysfunction prior to disturbed consciousness, with alcohol. The tablets, obtained online, were analysed by mass spectrometry and contained tadalafil and dapoxetine as advertised but also contained glimepiride. Learning points: Symptomatic unexplained hypoglycaemia requires investigation with plasma glucose level, c-peptide, insulin level, pro-insulin, beta-hydroxybutyrate, and a sulphonylurea screen regardless of known exposure to sulphonylureas. Consider contamination of alternative or undisclosed medication, including PDE-5 inhibitor erectile dysfunction drugs. Concomitant alcohol may impair glycogenolysis and gluconeogenesis, exacerbating hypoglycaemia.